PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA FISIK TERHADAP SEMANGAT KERJA KARYAWAN PADA UNIVERSITAS PGRI PALEMBANG - Heryati . (Universitas PGRI Palembang, 2015)
This Research aim to to know leadership influence and environment work physical either through parsial and also by together with spirit of Job Employees University PGRI Palembang. This Research population is all officer of University of PGRI Palmbang amounting to 416 people, while sample taken to amount to 83 people with the technique of random sampling. Instrument of data collecting used is enquette by using scale likert compiled by pursuant to construction embraced from various theory realized by into variable operational, while examination to research instrument conducted by passing validity test and test the reliabilitas. Analyse the data done by passing conditions test consisted of by the test normalitas using test kolmogorovsmirnov, test the homogeneity by using test of Chi Square and test the Linearity using One-Way Anova. Hypothesis Examination done to use the analysis of regresi and correlation. Result of research indicate that (1) by parsial there are influence which are positive and signifikan between leadership hotly work University PGRI Palembang employees. (2) By parsial also there are influence which are positive and signifikan [among/between] environment work physical hotly work University PGRI Palembang employees. (3) By together or simultan there are influence which are positive and signifikan between environment and leadership work physical hotly work employees. Kata kunci : leadership, environment work physical, Job Employees